Dinamika industri Roti Micky bagi kehidupan sosial-ekonomi Masyarakat Sisir 1993-2020 - Sya'fa Nabila Kurnia Wahyuda; Lutfiah Ayundasari (Historiography: Journal of Indonesian History and Education, 2022)
The industrial sector is one type of sector that is quite busy among the people of Indonesia. The industrial sector, it is divided into the food industry, which is further divided into types of business units, one of which is UMKM (Micro, Small and Medium Enterprises). Bread is a type of food that contains carbohydrates, protein, and gluten derived from wheat flour dough. This becomes the factor in the emergence of Micky’s Bread industry. The purpose of this article is to discuss and review the historical dynamics of Micky’s Bread industry and its impact on the Sisir community from 1993 to 2020. The research method used is the historical method which consists of heuristics, source criticism, and interpretation, and in the last step is historiography. The results and discussion of this article are (1) the history of Micky’s bread industry in 1993-2020, (2) the socio-economic conditions of the Sisir community, and (3) the influence of the Micky bread industry on the Sisir community.Sektor industri merupakan salah satu jenis sektor yang cukup ramai di kalangan masyarakat Indonesia. Dalam sektor industri terbagi atas industri pangan, dengan terbagi lagi atas jenis unit usaha salah satunya usaha mikro, kecil, dan menengah (UMKM). Roti adalah suatu jenis makanan yang mengandung karbohidrat, protein, dan gluten yang berasal dari adonan tepung terigu. Hal ini menjadi faktor kemunculan industri Roti Micky. Tujuan pembahasan artikel ini membahas dan mengulas dinamika sejarah industri Roti Micky dan dampaknya bagi masyarakat Sisir sejak tahun 1993-2020. Metode penelitian yang digunakan adalah metode historis yang terdiri dari heuristik, kritik sumber, interpretasi, dan di langkah terakhir adalah historiografi. Adapun hasil dan pembahasan artikel ini (1) Sejarah industri Roti Micky tahun 1993-2020, (2) Kondisi sosial-ekonomi masyarakat Sisir, dan (3) Pengaruh industri Roti Micky bagi masyarakat Sisir.